MTFP1 overexpression promotes the growth of oral squamous cell carcinoma by inducing ROS production. (19th December 2019) - Xiao, Tingying; Sun, Jian; Xing, Zhankui; Xie, Fuqiang; Yang, Lan; Ding, Wenjuan
Abstract: Mitochondrial fission process 1 (MTFP1) is a novel nuclear‐encoded protein that promotes mitochondrial fission. Increasing lines of evidence indicate that increased mitochondrial fission is involved in carcinogenesis and tumor progression. However, the expression and biological effects of MTFP1 in cancer development is still unclear, especially in oral squamous cell carcinoma (OSCC). In this study, we first evaluated the expression of MTFP1 in 12‐paired OSCC tumor and peritumor tissues. We then explored the effects of MTFP1 knockdown or overexpression on cell growth by cell proliferation, colony formation, cell cycle, and cell apoptosis assays. Furthermore, the mechanisms by which MTFP1 promoted OSCC cell growth were explored. Our results showed that MTFP1 is frequently overexpressed in OSCC tissues. Functional experiments revealed that MTFP1 promoted the growth of OSCC cells by inducing the progression of cell cycle and suppressing cell apoptosis. Mechanistically, MTFP1 overexpression‐mediated mitochondrial fragmentation and subsequent ROS production was found to be involved in the promotion of OSCC cell growth. Collectively, our study demonstrates that MTFP1 plays a critical oncogenic role in OSCC carcinogenesis, which may serve as a potential therapeutic target in the treatment of this malignance.